IMPROVING VOCABULARY MASTERY FOR ELEMENTARY STUDENTS USING VISUAL AIDS (An Action Research to the Fourth Grade Students of Madrasah Ibtidaiyah Negeri 1 Surakarta in 2010/2011 the Academic Year) - JANNAH, HENNITA MIFTAKHUL (2011)
This study aims at describing whether the technique of visual aids of pictures can able to improve the students vocabulary and how the implementation of appropriate technique in the teaching vocabulary at the fourth grade of Madrasah Ibtidaiyah Negeri 1 Surakarta. So, the problem of the research are the technique of using visual aids of pictures able to improve the students' vocabulary mastery and how is the implementation of appropriate technique in the teaching vocabulary. This research belongs to classroom action research. The action research was conducted in two cycles and carried out in four steps, namely planning, action, observation, and reflection. The data were taken from the result of observation done by teacher while the actions were being carried out, and from the result of the tests after the cycles had been implemented. The tests were in the form of pre test and post test. This research is conducted in the fourth grade of Madrasah Ibtidaiyah Negeri 1 Surakarta. The result of the research shows that the use of visual aids through pictures could improve the quality of the English teaching and learning process. Being taught with pictures the students become more active, more enthusiastic, more interested and more motivated in learning new words so the teaching and learning process became alive. The student's vocabulary improvement is reflected in the test scores. The result of tests indicated that the mean score of the pretest is 38.5, while the mean score of the post test is 86.5. So, there is a significant improvement of the students vocabulary mastery before and after the research done. It is 46, 0. Therefore it can be concluded that teaching vocabulary by using visual aids through pictures could improve the students' vocabulary mastery.